Daniel’s Seventy Weeks in Luke 1–2: Allusion or Illusion? Fulfilment or Prefiguration? - MacPherson, Anthony (Neotestamentica, 2023)
In the early 20th century, Eric Burrows (1940) and René Laurentin (1957) made the argument that Luke 1-2 features a 490-day period which is a deliberate allusion to Dan 9’s seventy weeks prophecy. This view has received some support but suffered its most significant pushback when Raymond Brown in 1977 dismissed it in his major work on the infancy narratives of Matthew and Luke. Brown’s criticisms have influenced later commentators (e.g., Bock 1994). This may account for the tentativeness of support, if it is mentioned at all, in contemporary Lucan commentaries. This article will first revisit the earlier view of Burrows and Laurentin and will offer a general defence of their basic position against Brown’s objections. However, limitations and problems in their position are recognised and discussed, and a new modified understanding of Luke’s allusion to Daniel’s seventy weeks will be advanced. It will be argued that Luke is not seeking to indicate that Daniel’s seventy weeks are being fulfilled in the birth of Jesus. Rather, Luke is showing that a complementary 490-day period in the infancy of John and Jesus prefigures their future work, and this parallels Daniel’s seventy-week prophecy. Luke either designs or discerns in the infancy of John and Jesus a miniaturised Daniel-like 490-day period which is also a prefiguration of the future of John and Jesus. The result is that Luke’s 490 days helps prepare the reader for the fulfilment in history of Daniel’s seventy-week prophecy in Luke 3-4.